PEDAGANG PASAR TIBAN DAN MODAL SOSIAL Membangun Tatanan Sosial-Ekonomi Lokal - Rismawati, Shinta Dewi (Jurnal Penelitian, 2010)
After the breaking off of Banjarsari market of Pekalongan City, the small vendors of the market came up and did not give up with the condition. They made an institution called PARTI or PASTI –standing for pasar tiban – to hold a temporary market to make them survive economically. The problems to be answered in this research are what the social capital values that are acknowledged and institutionalized among the vendors; how they struggle to survive; and what factors that support and hamper their struggle. To answer those problems, this research used qualitative approach by observation and in-depth interview to collect data. Key informants were selected purposively using snowball sampling. Data triangulation was used to validate the collected data. The result of this research shows that social capital values i.e. trust, values-norms, participation, and structure based on Islamic values and built up through social interaction between the vendors and their stakeholders can put the society’s economic wheel in motion and also build social structure more effective, efficient, and communicative. The ability strategy done by them to survive and exist is that they are able to maintain their ability in increasing their turnover, number of costumers, capital, and family’s welfare, and their ability to make good relationship among them, and between them and local community and administration. In fact, the existence of temporary market has not only support factors but also hamper factors